PENGARUH CRYPTOCURRENCY, INTELECTUAL CAPITAL, LEVERAGE DAN NILAI TUKAR RUPIAH TERHADAP NILAI SAHAM PERUSAHAAN, SEBELUM DAN PADA SAAT PANDEMI COVID-19 (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN DI BEI PERIODE JUNI 2019 - MARET 31, 2020) - Endang Purwaningsih; Chatarina Guntur Citra Mandiri (Media Akuntansi, 2021)
This study aims to determine the effect of Cryptocurrency, Intellectual Capital, Rupiah Exchange Rate, Leverage, and Return On Assets on stock prices. The objects of this research are banking companies listed on the IDX from June 2019 to March 2021. The sampling technique uses secondary data sources, namely data obtained or collected by researchers from various existing sources. The number of samples used as many as 46 banking companies. The analytical method used is the classical assumption test and multiple regression test. Based on the analysis conducted, it can be concluded that this study meets the requirements of the classical assumption test. Hypothesis testing using the t test shows that Cryptocurrency has no effect on stock prices before the Covid-19 Pandemic, and has a significant effect on stock prices during the Covid-19 Pandemic. Intellectual Capital has a significant positive effect on stock prices before Covid-19, and has no effect on stock prices during the Covid-19 Pandemic. Leverage has no effect on stock prices before and during the Covid-19 Pandemic. The Rupiah Exchange Rate has no effect on stock prices before and during the Covid-19 Pandemic. has a significant positive effect on stock prices before and during the Covid-19 Pandemic.